Valoración económica del servicio de secuestro de co2 en un bosque de colina baja del predio paraiso amazónico, distrito de Nauta, Loreto. 2022 - Flores Rios, Mayra (2023)
This study calculated the cost of the CO2 sequestration service provided by a low hill forest in the district of Nauta. The results of the forest census of commercial species in the low hill forest of the Paraíso Amazónico property were evaluated. According to the results, 1351 trees, 40 commercial forest species and 18 botanical families were discovered. The economic value of CO2 sequestration is 981,995.49 USD; the species with the highest economic value for CO2 sequestration are Allantoma decandra, Eschweilera juruensis, Parkia ulei, Brosimum rubescens and Brosimum utile. Allantoma decandra has the highest economic value for CO2 sequestration, with 124181,35 USD and 423,75 USD per hectare. The economic value of CO2 is lower in plants such as Otoba glycicarpa (5,74 USD/ha), Luehea cymulosa (4,65 USD/ha) and Hymenaea courbaril (4,64 USD/ha). The economic value of CO2 sequestration varies significantly ((α=0.05) depending on the species. It is recommended to include the carbon sequestration services provided by these forests in the carbon market.